Being pregnant, giving birth, and being a mother in the covid-19 pandemic: women's voices (Revista Contexto & Saúde, 2025)
This study aims at understanding the experience of pregnancy, delivery and motherhood during the Covid-19 pandemic in Ceara, Brazil. Qualitative exploratory research was carried out in Fortaleza, Ceara, from January to March 2022, with a sample of 30 women who were participants in a larger cohort study. The semistructured interviews was analyzed through the Thematic Oral History technique and Bardin's thematic content analysis method. The participants had an average age of 29.7 years. Most had one to two children, a monthly income equal to or less than one minimum wage, stable relationship and had not been affected by SARS-CoV-2. The analysis favored the emergence of three categories: challenges, feelings and experiences lived by participants about being pregnant, giving birth and being a mother in the Covid-19 pandemic. The findings suggest that the social isolation resulting from the Covid-19 pandemic, its socioeconomic impacts and the organization of health services resulted in negative experiences these experiences favoring the emergence of fear, anxiety, insecurity and stress. Thus, this article makes it possible to subsidize healthcare services to observe more humanized models for women in contexts of health crisis.